Anterior chamber depth and angle and associations in a pediatric and adult population in Russia - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Iakupova, Ellina M.; Gilmanshin, Timur R.; Fakhretdinova, Albina A.; Tuliakova, Azaliia M.; Panda-Jonas, Songhomitra; Miniazeva, Liana A.; Gilemzianova, Leisan I.; Khakimov, Dinar A.; Rusakova, Iuliia A.; Islamova, Liaisan I.; et al. (Heliyon, 2023)
Purpose: To investigate the normative data of anterior chamber depth (ACD) and angle (ACA) and their associations in multiethnic cohorts spanning three generations in Russia.Methods: The study cohort included the participants of three population-based studies performed in urban and rural Bashkortostan/Russia: The Ural Eye and Medical Study (UEMS; age:40+ years), Ural Children Eye Study (UCES; age:6-18 years), and Ural Very Old Study (UVOS; age:85+ years). Using Scheimflug camera-based anterior chamber imaging, we measured ACD and ACA as part of a comprehensive ophthalmological and systemic examination. Exclusion criterion was previous cataract surgery.Results: The study included 4869 (98.7 %) children out of 4933 children of the UCES, 5426 (92.0 %) out of 5899 UEMS participants, and 268 (16.3 %) out of 1526 UVOS participants. In the UEMS, shallower ACD (mean:3.14 +/- 0.37 mm) correlated (multivariable analysis; r[2] = 0.57) with older age (beta: 0.08;P < 0.001), shorter body height (beta:0.03;P = 0.003), shorter axial length (beta:0.34;P < 0.001), lower corneal volume (beta:0.06;P < 0.001) and corneal refractive power (beta:0.12;P < 0.001), thicker lens (beta: 0.09;P < 0.001), higher IOP (beta: 0.03;P = 0.02), higher prevalence of angle-closure glaucoma (beta: 0.03;P = 0.003) and lower prevalence of open-angle glaucoma (beta:0.03;P = 0.007). Similar associations were found in the UCES (ACD mean:3.70 +/- 0.27 mm) and UVOS (ACD mean:2.96 +/- 0.56 mm).Conclusions: In this population-based cohort of three generations from rural and urban Bashkortostan, ACD decreased from the children cohort (mean:3.70 +/- 0.27 mm) to the adult cohort (mean:3.14 +/- 0.37 mm) and to the very old cohort (2.96 +/- 0.56 mm). Determinants of shallow ACD were older age and lower body height, in addition to the ocular biometric parameters of shorter axial length, lower corneal volume, corneal refractive power, and thinner lens thickness.